2021
DOI: 10.1016/j.molcel.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of YTHDF2 triggers proteotoxic cell death in MYC-driven breast cancer

Abstract: RNA-binding proteins (RBPs) are critical regulators of post-transcriptional gene expression, and aberrant RBP-RNA interactions can promote cancer progression. Here, we interrogate the function of RBPs in cancer using pooled CRISPR-Cas9 screening and identify 57 RBP candidates with distinct roles in supporting MYCdriven oncogenic pathways. We find that disrupting YTHDF2-dependent mRNA degradation triggers apoptosis in triple-negative breast cancer (TNBC) cells and tumors. eCLIP and m 6 A sequencing reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 84 publications
1
110
0
Order By: Relevance
“…Previous studies have confirmed that the interaction of different YTH domain family proteins with m 6 A sites can have different effects on mRNA gene expression [ 33 ]. YTHDF2 can specifically recognize and bind to the single-stranded RNA sequence containing m 6 A through the YTH domain at the C-terminus, simultaneously promote co-localization with decay factors, and transport it to the P body to be degraded under the action of the N-terminus [ 34 ]. We speculate that METTL14 might inhibit the expression of ASS1 in an m6A-YTHDF2-dependent pathway, thereby promoting the occurrence and development of glioma.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have confirmed that the interaction of different YTH domain family proteins with m 6 A sites can have different effects on mRNA gene expression [ 33 ]. YTHDF2 can specifically recognize and bind to the single-stranded RNA sequence containing m 6 A through the YTH domain at the C-terminus, simultaneously promote co-localization with decay factors, and transport it to the P body to be degraded under the action of the N-terminus [ 34 ]. We speculate that METTL14 might inhibit the expression of ASS1 in an m6A-YTHDF2-dependent pathway, thereby promoting the occurrence and development of glioma.…”
Section: Resultsmentioning
confidence: 99%
“…YTHDF1 is reported to play a vital role in promoting translation in the cytosol, whereas YTHDF2 regulates mRNA degradation by mediating the lifetime of target transcripts [ 35 , 36 ]. Nonetheless, gene expression, cell death, and survival are associated with the YTHDF2-mediated RNA process [ 37 , 38 ]. YTHDF3 cooperates with YTHDF1 and YTHDF2 to affect the translation and decay of m6A-decorated mRNA, and inversely regulates their function [ 39 ].…”
Section: Molecular Composition Of the M6a Rna Methylation Regulatorsmentioning
confidence: 99%
“…Jie Wu et al proposed a ten-m6A-related LncRNAs as potential biomarkers to predict the prognostic risk of TNBC (34). Jaclyn M Einstein et al found that inhibition of YTHDF2 triggers proteotoxic cell death in MYC-driven breast cancer (35). However, rarely studies reported whether m 6 A methylation contributes to cell proliferation and metastasis in TNBC, and what underlying mechanisms are involved.…”
Section: Discussionmentioning
confidence: 99%